1991
DOI: 10.3109/07420529109059186
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacology of Captopril plus Hydrochlorothiazide in Hypertension: Morning Versus Evening Dosing

Abstract: Blood pressure follows a strong circadian rhythm in normotensive people and in patients with primary hypertension. This may have several implications for antihypertensive therapy, including the time of dosing. For this reason we studied the influence of different dosing times on the antihypertensive effect over 24 h using ambulatory blood pressure monitoring (ABPM). We studied 13 male patients with moderate hypertension with controlled blood pressure over 12 months under a fixed combination of captopril and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 2 publications
0
13
0
3
Order By: Relevance
“…Most, but not all, of these small sample-size investigations found greater effect of the evening schedule on the asleep than awake BP plus significant modification of the circadian BP profile towards a more normal dipping pattern. For example, Middeke et al [47] showed the combination of captopril and hydrochlorothiazide was slightly more effective in reducing night-time BP when administered in the evening, although Kohno et al [48] found no significant morning-evening, treatment-time difference in the control of the diurnal or nocturnal BP means with imidapril (10 mg/day) in their 20-patient crossover study.…”
Section: Chronotherapy With Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 97%
“…Most, but not all, of these small sample-size investigations found greater effect of the evening schedule on the asleep than awake BP plus significant modification of the circadian BP profile towards a more normal dipping pattern. For example, Middeke et al [47] showed the combination of captopril and hydrochlorothiazide was slightly more effective in reducing night-time BP when administered in the evening, although Kohno et al [48] found no significant morning-evening, treatment-time difference in the control of the diurnal or nocturnal BP means with imidapril (10 mg/day) in their 20-patient crossover study.…”
Section: Chronotherapy With Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 97%
“…When used in combination with other antihypertensive drugs, CCBs can exhibit a marked BP lowering effect and may induce a too potent hypotensive effect. [29][30] Third, too few ABPM measurements were obtained in this study; therefore, some data points with significant BP changes between these two regimens may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32] Greminger, et al studied the effect of morning versus evening administration of nifedipine gastrointestinal therapeutic system (GITS) in 15 patients with moderate hypertension and concluded that the time of administration of nifedipine GITS had no impact on daytime or nighttime BP control. 25) Mengden, et al reported that different timing of once-daily amlodipine administration does not influence its efficacy for 24-hour BP control.…”
Section: Discussionmentioning
confidence: 99%
“…Hier liegen prospektive Studiendaten vor, die sowohl das erhöhte Risiko bei Normabweichungen vom normalen Rhythmus zeigen, als auch für die individuelle Wahl des Dosierungszeitpunkts und der Dosierungsintervalle von Bedeutung sind [7,13,16,19,22]. Der saisonale Rhythmus mit höheren Werten im Winter [5] hat eine gewisse epidemiologische Bedeutung und ist am ehesten bedingt durch Kälte und Vitamin-D-Mangel.…”
unclassified
“…die morgendliche gegen abendliche Einnahme in Cross-over-Studien [13]. Die erste Untersuchung bei Patienten mit primärer Hypertonie erfolgte 1991 [16]. [26].…”
unclassified